2018
DOI: 10.1161/circulationaha.117.033359
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Blood Flow in Cardiovascular Disease

Abstract: Visualization and quantification of the adverse effects of distorted blood flow are important emerging fields in cardiology. Abnormal blood flow patterns can be seen in various cardiovascular diseases and are associated with increased energy loss. These adverse energetics can be measured and quantified using 3-dimensional blood flow data, derived from computational fluid dynamics and 4-dimensional flow magnetic resonance imaging, and provide new, promising hemodynamic markers. In patients with palliated single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 102 publications
0
41
1
Order By: Relevance
“…Continuous measurement of blood flow also plays an important role in the diagnosis and characterization of cardiovascular health by providing microvascular and macrovascular flow information regarding kinetic energy along its course through the body. Abnormal blood flow patterns caused by abnormal geometry of vessels or valves induce unavoidable frictional loss of energy, hence it may ultimately result in heart failure . There are several principles to measure blood flow including mechanical, optical, acoustic, and thermal methods.…”
Section: Soft Bioelectronics For Monitoringmentioning
confidence: 99%
“…Continuous measurement of blood flow also plays an important role in the diagnosis and characterization of cardiovascular health by providing microvascular and macrovascular flow information regarding kinetic energy along its course through the body. Abnormal blood flow patterns caused by abnormal geometry of vessels or valves induce unavoidable frictional loss of energy, hence it may ultimately result in heart failure . There are several principles to measure blood flow including mechanical, optical, acoustic, and thermal methods.…”
Section: Soft Bioelectronics For Monitoringmentioning
confidence: 99%
“…At the same time, there is a high risk of the cardiovascular system to fail due to various reasons such as ventricular dysfunction, elevated pulmonary vascular impedance, inadequate preload to the ventricle, increased neurohumoral activation, and elevated systemic venous pressure . In order to increase the patients’ survival rate and the quality of their life, along with different TCPC connections oriented to improve blood hemodynamics, mechanical circulatory support (MCS) is applied as another auspicious treatment option …”
Section: Introductionmentioning
confidence: 99%
“…Techniques described in modern studies allow the analysis of the blood flow behavior and improvement of the geometry of the TCPC connection. It was shown that 3D and 4D blood flow data received from computational fluid dynamics (CFD) and magnetic resonance imaging can be used for measuring the adverse energetics . Whereas multi‐scale modeling can be used for the simulation of the hemodynamic effects of the Fontan circulation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations